Performance analysis of stacking neural network and machine learning model for detecting fraudulent transaction - Chowdhury, Ahnaf Shahriyar; Abdullah, Nayeem; Mamun, Hasan Al (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.